The Magnitude and Determinants of Tinnitus among Health Science Students at King Khalid University - Abdullah Musleh; Salah Saad Alzahrani; Turki Khalid Al Shehri; Saad Mohammed Abdullah Alqahtani; Samar Yahya Ali Yahya; Ahmed Oudah Saeed AlShahrani (The Scientific World Journal)
Background. Tinnitus is a symptom that is defined as a subjective perception of noise in an absence of external sound. It is an indicator of auditory system abnormalities. It can also be present in individuals without any hearing abnormalities. Difficulty to consternate, insomnia, and decreased speech discrimination are the most common symptoms related to tinnitus. Aim. To assess the magnitude and pattern with determinants of tinnitus among health science students at King Khalid University. Methodology. A descriptive cross-sectional survey was conducted targeting all accessible students in health science colleges in King Khalid University which is the main university in the Aseer region, south of Saudi Arabia. Students were included consecutively from different faculties and different grades. Data were collected through a self-administered prestructured questionnaire, which was distributed and recollected the next day. Tinnitus was screened using an adapted form of the National Health and Nutrition Examination Survey (NHANES). Results. A total sample of 400 students have been included with their ages ranging from 18 to 30 years with a mean age of 22 ± 1.8 years), and 28.5% of the students recorded positive findings. Tinnitus was bilateral among 51.8% of students, and 44.7% of tinnitus students hear buzzing sound while 21.1% have hissing sound and 10.5% had pulsating sound. Among 46.5% of students with tinnitus, the heard sound was of moderate loudness and intermittent among 64.9% of them. Conclusions and Recommendations. In conclusion, the study revealed that just more than a quarter of students complained of tinnitus which was bilateral among half of them. Tinnitus frequency was mainly moderate in intensity and intermittent. Having ear problems, loud sounds, and allergy were the most important predictors of having Tinnitus.